PENGARUH TEKNOLOGI TERHADAP EFEKTIFITAS KINERJA KARYAWAN FOOD AND BEVERAGE DEPARTEMENT DI HOTEL AYANA BALI - Ni Made Candra Purwaningsih; Ni Luh Gde Sri Sadjuni; Ir. I Nyoman Sukana Sabudi (JURNAL BISNIS HOSPITALITI, 2026)
Technology development in the hospitality industry is accelerating, including operational and service aspects to improve efficiency and customer experience. AYANA Bali, a five-star hotel, implemented the AYANA App digital reservation application to support operations. However, there is a gap between technology utilization and work effectiveness in the FnB department which affects service speed and potential operational errors. This study describes the effect of AYANA App on operations, services, and employee work effectiveness from the aspects of goal achievement, quality, quantity, and timeliness. The sample included 75 food and beverage workers, using a questionnaire approach and data analysis conducted with SPSS version 26. The findings indicated that technology positively and significantly influences employee job performance, shown by a t-count of 9.783 and a significance level of 0.000, which is less than 0.05. The contribution of technology’s influence on work effectiveness is 56.7% including the medium category. The application of technology such as AYANA App has a positive impact on increasing the effectiveness of employee performance in the FnB department.